Perceptions and Preferences of Traditional Market Traders toward Islamic Banking - M. Fahrurrozi; Abidin, Zaenal; Sarwono; Khoiratun Nisak, Sayida; Dewi , Hasna; Musthofa , M. Arif; Kartika Devi, Erwina (Journal of Economics and Social Sciences (JESS), 2025)
This study explores the perceptions of traders at Pasar Sabtu, Mendahara Ilir, towards Islamic banking, focusing on factors influencing their acceptance and utilization of Sharia-compliant financial services. Employing a qualitative descriptive approach through interviews, observations, and document analysis, the research uncovers that while traders exhibit a positive inclination toward Islamic banking grounded in spiritual values and trust, their understanding of fundamental Sharia principles remains limited. Barriers such as restricted physical access to Islamic banking branches, inadequate financial and digital literacy, and reliance on informal information networks hinder broader adoption. The study highlights the critical role of spirituality as social capital, alongside geographic, educational, and socio-cultural factors, in shaping perceptions and behaviors. Findings suggest that for Islamic banking to expand inclusively within traditional markets, strategic emphasis must be placed on comprehensive literacy enhancement, improved accessibility, and community engagement. This research contributes novel insights by holistically integrating spiritual, educational, and socio-economic dimensions, providing a foundation for tailored educational and marketing strategies that support sustainable financial inclusion